2018
DOI: 10.3390/s18092908
|View full text |Cite
|
Sign up to set email alerts
|

Early Fault Diagnosis for Planetary Gearbox Based Wavelet Packet Energy and Modulation Signal Bispectrum Analysis

Abstract: The planetary gearbox is at the heart of most rotating machinery. The premature failure and subsequent downtime of a planetary gearbox not only seriously affects the reliability and safety of the entire rotating machinery but also results in severe accidents and economic losses in industrial applications. It is an important and challenging task to accurately detect failures in a planetary gearbox at an early stage to ensure the safety and reliability of the mechanical transmission system. In this paper, a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…To suppress noise and extract the fault-related sidebands accurately, MSB method is used in this study. According to the definition of MSB in the frequency domain, for gear vibration signal x(t) with corresponding Fourier transform (FT) X(f ), the MSB-SE can be defined in the frequency domain as [17][18][19].…”
Section: Modulation Signal Bispectrum-based Sideband Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…To suppress noise and extract the fault-related sidebands accurately, MSB method is used in this study. According to the definition of MSB in the frequency domain, for gear vibration signal x(t) with corresponding Fourier transform (FT) X(f ), the MSB-SE can be defined in the frequency domain as [17][18][19].…”
Section: Modulation Signal Bispectrum-based Sideband Estimationmentioning
confidence: 99%
“…Bispectrum analysis is a useful signal processing tool that has shown significant benefits over traditional spectral analyses due to its unique properties of nonlinear system identification, Gaussian noise elimination, and phase information retention [14][15][16][17][18][19][20][21]. Conventional bispectrum (CB) was applied to vibration signals for the detection of different degrees of tooth breakage of a two-stage helical gearbox and tooth crack [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Resample the sensors' data based on the frames. Many studies have shown that any type of fault in the planetary gearbox will lead to the development of mechanical vibrations, and by examining the changes in characteristic frequency spectrum around the mesh frequency and its harmonics, these faults can be detected and diagnosed [3]. Assuming that K is the number of planetary gears that are moving within the carrier, the characteristic vibration frequencies around the meshing frequency are unique for each type of planetary gearbox fault, as identified by [4].…”
Section: Ax3mentioning
confidence: 99%
“…Since the applications of planetary gearboxes are quite critical and their failure may cause shutdown of the entire train resulting in major economic losses, condition monitoring of planetary gearboxes has received significant attention from many researchers. To avoid any unexpected interruptions and accidents that might be caused by planetary gearbox failure [3,4]. , many studies have recently been carried out into the development of planetary gearbox condition monitoring and fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%